KELUAR DARI TEKANAN: KONSTRUKSI GERAKAN SYI’AH DI YOGYAKARTA: (Studi Terhadap Lembaga Rausyan Fikr) - Muhammad Taufik (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
The Sunni and Shia’s conflict was occurred during contestation between the majority and minority people. In Indonesia, Sunnis are majority which naturally had a position that would always suppress the minority, however there is a subordination of those who have power to the ruled. For this reason, for those people who have been controlled will always be controlled and oppressed, so that all activities will be limited. This issues were happened in Yogyakarta, where the Shi’a group named Rausyan Fikr was oppressed and harassed by a pressure community consisting of the Islamic Community Forum (FUI) and the Islamic Jihad Front (FJI). The pressure communities consider the Shi’a group Rausyan Fikr have spread heresy or heterodoxy which is contrary to the creed of the Sunni majority. The oppressed communities are raising theological and aqidah issues that the Shi’a of Rausyan Fikr are Shi'a rafidhah who are heretic and unbeliever. But on the other hand, the Shi’a group (Rausyan Fikr) operates in the realm of thought and philosophy, not in the theological and religious areas which are considered to be the private domain. In responding to this problem, the Shi’a group (Rausyan Fikr) could be goodin their strategy so they can get out of pressure. As a result, the Shi’a group took strategy through the spiral of silence movement by utilizing the mass media as a purpose to spread discourse that would supported their action. In addition, Rausyan Fikr develops activities that can support their mobility such as building an intellectual movement of the Islamic Philosophy Activist Network (JAKFI) which focuses on areas of science and philosophy.